Factors associated with early adolescents’ anticipated emotional and behavioral responses to ambiguous teases on Facebook - Barnett, Mark A.; Nichols, Marcella B.; Sonnentag, Tammy L.; Wadian, Taylor W. (My University, 2013)
A total of 69 sixth- through eighth-grade students rated their experiences with antisocial and prosocial teases as well as their general attitudes toward teases. Subsequently, the participants read hard copies of four ambiguous teases, one at a time, posted on a simulation of “their” Facebook wall by four different, hypothetical acquaintances. After reading each tease, the participants were asked to complete a questionnaire that assessed their emotional and behavioral response to the tease. Consistent with Weiner's (1980, 1995) cognitive (attribution)-emotion-action model of motivated behavior, path analyses revealed that the participants’ negative experiences with teases and negative attitudes toward teases were predictive of a negative emotional response to the ambiguous teases on Facebook which, in turn, was predictive of various negative behavioral responses to the ambiguous teasers. Therefore, consistent with the prior finding of a hostile attribution bias in some children’s reactions to ambiguous face-to-face teases (Barnett, Barlett, Livengood, Murphy, & Brewton, 2010), the early adolescents in the present study with relatively negative experiences with and attitudes toward teases appear to display a hostile attribution bias whereby teases on Facebook with an uncertain intent are viewed as if they were meant to be antagonistic and antisocial.
Keywords: Teasing; Hostile attribution bias; Peer relations; Facebook